The Effect Of Self-Management Education On The Quality Of Life Of Patients With Type 2 Diabetes Mellitus - Rahmat Pannyiwi; Azmi Wijayati; Enka Nur Ishmatica; Dwi Ardyna Octa Sari; Suwardha Yunus (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background : Type 2 diabetes mellitus is a chronic disease that requires continuous Inadequate self- management self-management May affect disease control and reduce patients ' quality of life . Self-management education is an important approach to improve patients ' knowledge , skills , and ability to manage diabetes daily life. Objective : This study aimed to determine the effect of self-management education on the quality of life of patients with type 2 diabetes mellitus. Methods : This study used a quantitative quasi-experimental design with a pretest-posttest control group approach . The respondents consisted of 80 patients with type 2 diabetes mellitus , divided into an intervention group (n=40) and a control group (n=40). The intervention group received structured self-management education covering dietary management , physical activity , medication adherence , blood glucose monitoring , foot care , prevention of complications , stress management , and healthy lifestyle . Quality of life was measured before and after the intervention. Results : The mean quality of life score in the intervention group increased from 61.45 before the intervention to 73.20 after the intervention , with an increase of 11.75 points . In the control group , the mean score increased from 60.90 to 63.10, with an increase of 2.20 points . Statistical analysis showed a significant difference in quality of life changes between the intervention and control groups ( p < 0.001 ). Conclusion : Self-management education had a significant positive effect on improving the quality of life of patients with type 2 diabetes mellitus .